Exploring aversion loss: a theoretical perspective over behavioral positive and negative markers - Marcu, Radiana; Rad, Gavril; Rad, Dana (Technium Social Sciences Journal, 2024)
In this article, we explore the phenomenon of loss aversion within the domain of behavioral economics, emphasizing the different perceptions individuals hold toward losses and gains. Loss aversion, a concept present in psychological literature, delineates why individuals manifest more intense emotional and psychological responses to losses than to gains of similar magnitude. By integrating contemporary research and empirical evidence, this study utilizes thematic analysis and narrative review to investigate the cognitive and affective processes that underlie loss aversion. This approach provides a theoretical understanding of how these processes affect decision-making and behavioral patterns. Furthermore, the study investigates the behavioral manifestations associated with both positive and negative outcomes within the context of loss aversion. This narrative review not only enhances our comprehension of human decision-making mechanisms but also presents insights with implications for both theoretical frameworks and practical interventions.